Judô e jiu-jítsu e o desenvolvimento integral de crianças em séries escolares iniciais - Schuler, Suely (2007)
The total development of children in the elementary school grades, particularly from six to twelve years old, and who participate of the Project Judo / Jiu-Jitsu are the themes from this dissertation. How the Project Judo / Jiu-Jitsu helps the child s growth is the main question. The first chapter is referred to the development and the learning focusing on the "psychomotricity", because this sees the child as a whole. Another aspect is the child development in its emotional, cognitive, social, religious and moral characteristics, for a better understanding and interaction of the adult with the child in this phase. From the bibliography consulted, observations and children s, from the Project Judo / Jiu-Jitsu, accompaniment the author noticed a better development of these, because child is movement and games are indispensable for them. It is society s duty, in special from the educational institutions, develop the maximum of the potentialities and minimize the "inner prisons". The child when living the "resonances of the care", as, the cordiality, the share, the compassion, will adequately develop, be happier and irradiate these echoes from caring to others, to the child itself, and to the environment.